A study on combat process simulation and casualty forecasting based on system dynamics. (March 2020) - Peng, B; Xu, L; He, Zh
Abstract: The traditional casualty prediction method is of low accuracy, and there is no prediction of the detail time and place of the casualty. Moreover, there is no consideration of the real combat environment. This study uses system dynamics method to build casualty forecasting model, based on the dynamic combat process of red and blue troops to predict the temporal and spatial distribution of casualty. The simulation results are similar to the one actual case. Results show that the modern combat has short duration and the total number of casualties declined over the past but the casualty is concentrated in a short period of time, and attributed in wider areas. Air forces and relative military strength are the key influence factors for casualty. The use of system dynamics model for casualty prediction can significantly improve the pertinence and effectiveness of medical support.